The heat never bothered me anyway: Gender‐specific response of agricultural labor to climatic shocks in Tanzania - Lee, Yeyoung; Haile, Beliyou; Seymour, Greg; Azzarri, Carlo (Agricultural and Applied Economics Association, 2021)
Agricultural production in Africa is generally highly labor intensive with gender‐specific specialization across activities. Using panel data from Tanzania, we examine the effects of heat stress (temperature above 29°C) during the maize‐growing season on gender‐disaggregated agricultural labor use. Results show that heat stress reduces total male family labor but does not statistically affect female family labor. Households with only female adults seem to increase their labor supply under heat stress. Given these heterogeneous effects, gender‐sensitive development interventions and adaptation strategies are suggested to enhance women's adaptive capacity.